Wuras’s complicity in the ’construction’ of the colonial Korana through his knowledge of the !Ora - Erasmus, P. (Southern African Humanities, 2012)
Through his contact with the Korana during the nineteenth century, Rev. Carl F. Wuras became a principal agent in the construction, development and preservation of !Ora in its written form. However, over a fifty-year period he also contributed to a colonial discourse that created and advanced a highly stereotyped and tarnished image of the Korana, so much so that Korana descendents have distanced themselves from the markers of their descent, including their language, in an attempt to escape the stigma attached to them. The result has been a general perception that the Korana have ’disappeared’ and that their language, !Ora, now survives mainly in written form. It is only now, after nearly two centuries, that Wuras’s colonial legacy, his contribution to the development of written !Ora, has led to an unexpected upswing in Korana identity. This article therefore focuses on Wuras’s contribution to the development of written !Ora, his role in the establishment and development of two mission stations, and his participation in the colonial discourse that was responsible for the ’construction’ of the colonial Korana.